Sarcocystis spp. infection in South American deer huemul (Hippocamelus bisulcus) and pudu (Pudu puda) from Patagonian National Parks, Argentina - Chang Reissig, Elizabeth; Helman, Elisa; Moré, Gastón (Springer, 2020)
Sarcocystis spp. are intracellular protozoan parasites with heteroxenous life cycles. This study described Sarcocystis spp. infection in adult South American native deer huemul (Hippocamelus bisulcus) and pudu (Pudu puda). Heart, diaphragm, tongue, and skeletal muscle samples were collected from 5 huemuls and 2 pudus, found dead in National Parks. Direct microscopic examination, transmission electron microscopy, PCR, and sequencing were performed. Sarcocystis spp. microscopic thinwalled cysts were identified in 3 huemuls and 1 pudu. Several cysts from 1 huemul and 1 pudu were observed by TEM; ultrastructure was similar to previously reported as cyst wall type 17 and types 2 and 8, respectively. Fragments of the 18S rRNA and cytochrome c oxidase subunit I (cox1) genes were amplified and sequenced from 3 individual cysts from 2 huemuls and 2 cysts from the pudu. The sequences from huemuls showed a high identity among them (> 99%) at both amplified targets. The highest identities were > 99.7% at 18S rRNA and 93% at cox1 with S. tarandivulpes sequences. The 18S rRNA gene sequences from pudus showed an identity > 99.7% with Sarcocystis sp., S. taeniata, and S. linearis sequences, while the cox1 sequences were different, one showing 99.42%identity with S. venatoria and the other 98.22%with S. linearis. A single species, similar to S. tarandivulpes, was identified in all huemul samples while 2 molecularly different Sarcocystis spp. were found in 1 pudu with high similarities to either S. venatoria or to S. linearis, S. taeniata-like, and S. morae. Based on the cox1 sequence identities, at least the Sarcocystis sp. in huemuls might represent a new species, primarily occurring in this host. Additional sarcocyst isolates from both hosts need to be examined molecularly in order to firmly establish whether these species are indeed native to huemuls and/or pudus or are derived from introduced deer species.